(untitled) (The Arab Journal of Administration, 2026)
This research aims to analyze the factors influencing customer intentions to embrace digital-only banking services in the public banking system of Egypt, primarily focusing on perceived value and trust as crucial mediating factors. The research builds on the Technology Acceptance Model and related adoption theories to explore the impact of five principal dimensions - perceived usefulness, perceived ease of use, perceived risk, digital financial literacy, and social influence - on customer adoption intentions. The study was based on a quantitative survey with 468 Egyptian public banks customers and was analyzed using Structural Equation Modeling with AMOS. For the measurement model, the fit indices were in the excellent ranges; model constructs showed high reliability and validity. For the 8 latent variables and 38 observed variables, the fit indices were: χ²/df = 1.558, RMSEA = .034, CFI = .965, TLI = .961. The analysis of the direct and indirect hypotheses was accomplished via structural model analysis, and the direct of the hypotheses constructs results were (p < .05). The most substantial influence in the perceived value dimensions was perceived usefulness (β = 0.834, CR = 20.927), and social influence showed a positive impact (β = 0.818, CR = 6.476). The perceived risk showed the contrary, where it negatively impacted the adoption (β = -0.538, CR = 9.640). The results for perceived value and trust showed a significant positive influence on adoption intention, where they accounted for 45.3% of the intention to use a digital-only bank (R² = 0.453). The research shows the importance of perceived value and trust, which is crucial for digital banking practitioners and policymakers in developing countries to understand because it enhances financial inclusion in Egypt.